Investor reactions to withdrawal of acquisition announcements. - Sew, Zi Xuan. (2011)
This paper examines the abnormal returns for acquiring firms when announced acquisitions are subsequently withdrawn and how it is influenced by the following factors: abnormal returns during announcement date, investors’ perceived likelihood of acquisition withdrawal, quality of corporate governance and CEO hubris. In addition, we conduct tests on the abnormal returns of target firms. Using a sample composing of publicly listed U.S. firms that withdraw from announced acquisitions over a ten-year period from 1998 to 2007, we find that acquiring firms experience positive abnormal returns upon withdrawing from an announced acquisition. We also find that the more negative the abnormal returns of acquiring firms upon acquisition announcement, the more positive the abnormal returns upon subsequent withdrawal. Conversely, investors’ perceived likelihood of withdrawal and target firms’ abnormal returns upon withdrawal are negatively associated with acquiring firms’ abnormal returns upon withdrawal. Corporate governance variables generally produce insignificant results, but we established a negative association between proportion of equity ownership by inside directors and abnormal returns of acquiring firms upon withdrawal. Acquiring firms’ CEO hubris is negatively correlated to the abnormal returns of the acquiring firms upon withdrawal while we find no significant result for the target firms’ CEO hubris.